The effects of storage temperature on the growth of Vibrio parahaemolyticus and organoleptic properties in oysters - Meshack eMudoh; Salina eParveen; Jurgen eSchwarz; Tom eRippen; Anish eChaudhuri (Frontiers Media S.A., 2014)
During harvesting and storage, microbial pathogens and natural spoilage flora may grow, negatively affecting the composition and texture of oysters and posing a potential health threat to susceptible consumers. A solution to these problems would mitigate associated damaging effects on the seafood industry. The purpose of this study was to investigate the effects of storage temperature on growth of Vibrios as well as other microbial, sensory and textural characteristics of post-harvest shellstock Eastern oysters (Crassostrea virginica). Oysters harvested from the Chesapeake Bay, Maryland, during summer months (June, July, and August, 2010) were subjected to three storage temperatures (5, 10, and 20ºC) over a 10 day period. At selected time intervals (0, 1, 3, 7, 10 days) two separate samples of 6 oysters each were homogenated and analyzed for pH, halophilic plate counts (HPC), total Vibrios, and Vibrio parahaemolyticus (Vp). Oyster meats shucked after storage were also organoleptically evaluated (acceptability, appearance, and odor). Texture analysis was performed using a texture analyzer on meats shucked from oysters held under the same conditions. The pH of the oyster homogenates showed no consistent pattern with storage time and temperature. The HPC (4.5 to 9.4log CFU/g) were highest on day 7 at 20C while olfactory acceptance reduced with time and increasing storage temperatures. The Vp counts increased over time from 3.5 to7.5 log MPN/g by day10. Loss of freshness as judged by appearance and odor was significant over time (p < 0.05). Toughness of oysters increased with storage time at 5 and 10ºC from day 1 to day 3, but was inconsistent after day 7. The results indicate that the length of storage and temperature had a significant effect on bacterial counts and olfactory acceptance of oysters but had an inconsistent effect on texture.